Synthesis and Evaluation of Antiproliferative Activity, Topoisomerase IIα Inhibition, DNA Binding and Non-Clinical Toxicity of New Acridine–Thiosemicarbazone Derivatives - Gleyton Sousa; Maria C. F. de Almeida; Lucas L. Lócio; Vanda L. dos Santos; Daniel P. Bezerra; Valdenizia R. Silva; Sinara M. V. de Almeida; Alice Simon; Thiago da S. Honório; Lucio M. Cabral; Rosane N. Castro; Ricardo O. de Moura; et al. (Pharmaceuticals, 2022)
In this study, we report the synthesis of twenty new acridine–thiosemicarbazone derivatives and their antiproliferative activities. Mechanisms of action such as the inhibition of topoisomerase IIα and the interaction with DNA have been studied for some of the most active derivatives by means of both in silico and in vitro methods, and evaluations of the non-clinical toxicities (in vivo) in mice. In general, the compounds showed greater cytotoxicity against B16-F10 cells, with the highest potency for DL-08 (IC50 = 14.79 µM). Derivatives DL-01 (77%), DL-07 (74%) and DL-08 (79%) showed interesting inhibition of topoisomerase IIα when compared to amsacrine, at 100 µM. In silico studies proposed the way of bonding of these compounds and a possible stereoelectronic reason for the absence of enzymatic activity for CL-07 and DL-06. Interactions with DNA presented different spectroscopic effects and indicate that the compound CL-07 has higher affinity for DNA (Kb = 4.75 × 104 M−1; Ksv = 2.6 × 103 M−1). In addition, compounds selected for non-clinical toxicity testing did not show serious signs of toxicity at the dose of 2000 mg/kg in mice; cytotoxic tests performed on leukemic cells (K-562) and its resistant form (K-562 Lucena 1) identified moderate potency for DL-01 and DL-08, with IC50 between 11.45 and 17.32 µM.